Upaya Hukum Penyelesaian Sengketa Konsumen dalam Transaksi E-Commerce di Luar Pengadilan - Abd. Rosid; Ahmad Musadad (Pemuliaan Keadilan, 2025)
The use of the internet is not only limited to utilizing information that can be accessed via social media, but can also be used as a means to carry out trade transactions that have been introduced in Indonesia, namely e-commerce. In e-commerce transactions in cyberspace, it is possible for disputes to occur, just like disputes that occur in a conventional legal relationship. The more numerous and extensive trading activities and e-commerce transactions, the higher the frequency of disputes and this means that there will be many disputes that must be resolved. One of the payments in e-commerce is COD (Cash On Delivery) which is made on the spot after the order from the courier is received by the buyer. In fact, there have been several cases that have resulted in losses felt by the seller in a buying and selling transaction via e-commerce. How to alternatively resolve consumer disputes through an out-of-court settlement process, and how to provide legal protection for consumers and business actors.